Design of sliding mode control optimised by the Bees algorithm for LFC in the Great Britain power system. (2022) - Shouran, Mokhtar; Anayi, Fatih; Packianather, Michael
Abstract: A design of Sliding Mode Control (SMC) is proposed in this work for Load Frequency Control (LFC) in the simplified Great Britain (GB) power system. The sliding surface of the proposed design has been identified to have five parameters. In order to guarantee the best usage of the proposed SMC design, the optimal gains of this controller are optimised by the Bees Algorithm (BA) and Particle Swarm Optimisation (PSO); the optimizations are conducted by employing the Integral Time Absolute Error (ITAE) objective function. A step load perturbation is applied to study the dynamic response of the system. The supremacy of the proposed approach is proved by comparing the results obtained with that from Proportional Integral Derivative (PID) controller tuned by BA. It is observed that the BA optimised SMC offers the best dynamic performance among the investigated techniques. Moreover, the results demonstrate the robustness of the proposed SMC based BA controller against system parametric uncertainties.